2020
DOI: 10.1111/risa.13471
|View full text |Cite
|
Sign up to set email alerts
|

Insights From Modeling Preventive Supplemental Immunization Activities as a Strategy to Eliminate Wild Poliovirus Transmission in Pakistan and Afghanistan

Abstract: Many countries use supplemental immunization activities (SIAs) with oral poliovirus vaccine (OPV) to keep their population immunity to transmission high using preventive, planned SIAs (pSIAs) and outbreaks response SIAs (oSIAs). Prior studies suggested that investment in pSIAs saved substantial health and financial costs due to avoided outbreaks. However, questions remain about the benefits of SIAs, particularly with the recent introduction of inactivated poliovirus vaccine (IPV) into routine immunization in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…We also run a final scenario (RC2*) that combines the assumptions in RC2 with the alternative reference case (RC*) from another paper (Kalkowska & Thompson, 2020), in which the WPV1 endemic countries improve the quality of planned, preventive SIAs (pSIAs) with bOPV such that global WPV1 eradication occurs before 2023. RC2* also assumes that all OPV+IPV using countries maintain bOPV pSIAs until globally coordinated bOPV cessation on January 1, 2025.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also run a final scenario (RC2*) that combines the assumptions in RC2 with the alternative reference case (RC*) from another paper (Kalkowska & Thompson, 2020), in which the WPV1 endemic countries improve the quality of planned, preventive SIAs (pSIAs) with bOPV such that global WPV1 eradication occurs before 2023. RC2* also assumes that all OPV+IPV using countries maintain bOPV pSIAs until globally coordinated bOPV cessation on January 1, 2025.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty years after the initial target date for polio eradication, the Global Polio Eradication Initiative (GPEI) is off track in the remaining endemic countries (Kalkowska, Wassilak, Cochi, Pallansch, & Thompson, 2020), with serotype 1 wild poliovirus (WPV1) expected to continue in Pakistan and Afghanistan through 2023. Additional modeling suggests that substantial improvements in the quality of coverage achieved with oral poliovirus vaccine (OPV) immunization activities in endemic countries could stop WPV1 transmission (Kalkowska & Thompson, 2020). In addition, although the GPEI globally coordinated the cessation of serotype 2 OPV (OPV2) in 2016, as of early 2020, outbreaks of vaccine‐derived polioviruses (VDPVs), particularly serotype 2 circulating VDPVs (cVDPV2s) (World Health Organization Global Polio Eradication Initiative, 2020a), continue to pose challenges and necessitate the use of serotype 2 monovalent OPV (mOPV2) for outbreak response.…”
Section: Introductionmentioning
confidence: 99%
“…During the next few years, the success or failure of the 2016 globally coordinated OPV2 cessation will become clear, and global health leaders will evaluate their commitments to OPV cessation as a polio endgame strategy [ 80 ]. Modeling published in early 2020 suggests that the GPEI remains off track with respect to achieving WPV1 eradication and successful OPV2 cessation [ 202 ], although WPV1 eradication remains possible with sufficiently high-intensity OPV vaccination [ 236 , 237 ]. Further modeling can help to quantify the probability of needing to restart OPV2, which a 2020 statistical analysis [ 238 ] and modeling study suggest appears likely [ 239 ].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Modeling suggests that the GPEI can still achieve eradication of all WPVs (Kalkowska & Thompson, 2020). However, if the GPEI and countries cannot achieve and maintain high population immunity to transmission for all three serotypes until successfully stopping all OPV and ensure that they successfully stop all OPV, then they may need to declare WPV1 eradication as not feasible and/or abandon the strategy of OPV cessation after WPV eradication altogether.…”
Section: Discussionmentioning
confidence: 99%
“…This would represent a substantial disappointment and missed global opportunity, not only for polio, but probably for future global public health major projects, including other disease eradication efforts. We recently suggested that WPV1 eradication is possible, with a commitment to high coverage bOPV use in Pakistan and Afghanistan (Kalkowska & Thompson, 2020). With the expenses of the GPEI mounting at an accelerated rate given its adoption of IPV and the failure to stop the transmission of WPV1 and cVDPV2s to date, challenges to the GPEI will likely include financial risks that may prove particularly problematic.…”
Section: Discussionmentioning
confidence: 99%